Evaluation of shoulder function in clavicular fracture patients after six surgical procedures based on a network meta-analysis. Issue 2 (16th January 2017) - Huang, Shou-Guo; Chen, Bo; Lv, Dong; Zhang, Yong; Nie, Feng-Feng; Li, Wei; Lv, Yao; Zhao, Huan-Li; Liu, Hong-Mei
Abstract: Purpose Using a network meta-analysis approach, our study aims to develop a ranking of the six surgical procedures, that is, Plate, titanium elastic nail (TEN), tension band wire (TBW), hook plate (HP), reconstruction plate (RP) and Knowles pin, by comparing the post-surgery constant shoulder scores in patients with clavicular fracture (CF).Methods A comprehensive search of electronic scientific literature databases was performed to retrieve publications investigating surgical procedures in CF, with the stringent eligible criteria, and clinical experimental studies of high quality and relevance to our area of interest were selected for network meta-analysis. Statistical analyses were conducted using Stata 12.0.Results A total of 19 studies met our inclusion criteria were eventually enrolled into our network meta-analysis, representing 1164 patients who had undergone surgical procedures for CF (TEN group = 240; Plate group = 164; TBW group  =  180; RP group  =  168; HP group  =  245; Knowles pin group  =  167). The network meta-analysis results revealed that RP significantly improved constant shoulder score in patients with CF when compared with TEN, and the post-operative constant shoulder scores in patients with CF after Plate, TBW, HP, Knowles pin and TEN were similar with no statistically significant differences. The treatment relative ranking of predictive probabilities of constant shoulder scores in patients with CF after surgery revealed the surface under the cumulative ranking curves (SUCRA) value is the highest in RP.Conclusion The current network meta-analysis suggests that RP may be the optimum surgical treatment among six inventions for patients with CF, and it can improve the shoulder score of patients with CF. Implications for Rehabilitation: RP improves shoulder joint function after surgical procedure. RP achieves stability with minimal complications after surgery. RP may be the optimum surgical treatment for rehabilitation of patients with CF.